Raids against LGBT as Fake Moral Agenda: a Study on News Media in Indonesia - Sari Andajani; Dinar Lubis; Sharyn Graham-Davies (Yayasan Jurnal Perempuan, 2015)
As a signatory to the Beijing Convention, Indonesia has the responsibility to live up to certain expectations, one of these is to safe guard human rights and the right to freedom of sexuality and access to sexual health. In this article we show this is not the case. In particular, because police are allowed to conduct raids on hotels and people are too scared to be open about their sexuality. As a result of being scared, people are not able to access sexual health care. Police raids are imposing a sexual morality agenda and the media is exploiting such raids by using horrific pictures, denigrating language maintaining stigmatization. If Indonesia is to get serious about HIV prevention, discrimination against GBV, police raids and violence against LGBT must stop.